The Apparent Authority of the Unauthorised Agent: Kelly v Fraser - LEE, Pey Woan (Institutional Knowledge at Singapore Management University, 2014)
Can an agent who is not authorised to contract for a company nevertheless be clothed with ostensible authority to communicate the principal's approval? Conventional understanding of apparent authority may suggest not, for the representation as to the principal's approval may be no different from the agent's self-authorisation. However, the controversial case of First Energy v Hungarian International Bank Ltd [1993] 2 Lloyd's Rep 194 ("First Energy") has held otherwise. Although the correctness of First Energy has been doubted, it has recently been unequivocally affirmed by the Privy Council in Kelly v Fraser [2012] 3 WLR 1008. This note considers how Kelly v Fraser may affect the reception of First Energy in Singapore.